208k views
2 votes
Solve the system of equations by using substitution

Y=2x+3
Y=x+2

User Kel Solaar
by
6.1k points

1 Answer

6 votes

Y = 2x + 3

Y = x + 2

Since our first equation reads y = 2x + 3, we can substitute a 2x + 3

in for y in our second equation and then solve from there.

So we have 2x + 3 = x + 2.

Now subtract x from both sides to get x + 3 = 2.

Now subtract 3 from both sides to get x = -1.

To find y, plug -1 back into either equation.

I have chosen to plug it into the second.

So we have y = (-1) + 2 which simplifies to 1.

So our solution to this system is (-1, 1).

User Shonni
by
5.7k points